Cost and contribution margin of transcatheter versus surgical aortic valve replacement - McCarthy, Fenton H. (J Thorac Cardiovasc Surg, 2017)
OBJECTIVE: To compare the cost of and payments for transcatheter aortic valve replacement (TAVR), a novel and expensive technology, and surgical aortic valve replacement (SAVR). METHODS: Medicare claims provided hospital charges, payments, and outcomes between January and December 2012. Hospital costs and charges were estimated using hospital-specific cost-to-charge ratios. Costs and payments were examined in propensity score– matched TAVR and SAVR patients. RESULTS: Medicare spent $215,770,200 nationally on 4083 patients who underwent TAVR in 2012. Hospital costs were higher for TAVR patients (median, $50,200; interquartile range [IQR], $39,800-$64,300) than for propensity-matched SAVR patients ($45,500; IQR, $34,500-$63,300; P < .01), owing largely to higher estimated medical supply costs, including the implanted valve prosthesis. Postprocedure hospital length of stay (LOS) length was shorter for TAVR patients (median, 5 days [IQR, 4–8 days] vs 7 days [IQR, 5–9 days]; P < .01), as was total intensive care unit (ICU) LOS (median, 2 days [IQR, 0–5 days] vs 3 days [IQR, 1–6 days]; P < .01). Medicare payments were lower for TAVR hospitalizations (median, $49,500; IQR, $36,900-$64,600) than for SAVR (median, $50,400; IQR, $37,400-$65,800; P < .01). The median of the differences between payments and costs (contribution margin) was –$3380 for TAVR hospitalizations and $2390 for SAVR hospitalizations (P < .01). CONCLUSIONS: TAVR accounted for $215 million in Medicare payments in its first year of clinical use. Among SAVR Medicare patients at a similar risk level, TAVR was associated with higher hospital costs despite shorter ICU LOS and hospital LOS. Overall and/or medical device cost reductions are needed for TAVR to have a net neutral financial impact on hospitals. (J Thorac Cardiovasc Surg 2017;154:1872–80)